"LEAVING TALK". ANDEAN COLONIAL STUDIES (CENTURIES XVI A.C. to XVIII A.C.) BY OTHER VERSION: NATIVE VOICE FROM THE PAINTED WOODEN CUPS TYPE LLIMPISCCAQUERO - Lizárraga Ibáñez, Manuel (2012)
The changes in the world wide order have resonance to the interior of the academic area. Thus after the loss of the universal hegemony of West and with this one, the fall of his euro-centric knowledge matrix: scientific and rational (modern according to Immanuel Kant); there began social and human studies that were trying to search, principally, the other voices that they were finding to the margin -silenced- by mentioned western knowledge matrix (as the Andean colonial rationality, for example). In this sense, the present essay will try to recover the voices of the Andean colonial societies across the study of his pre-Hispanic support systems («ethno-support») that they continued circulating -but reconfigured- inside colonial context; especially: the low relief painted wooden cups type llimpisccaquero (16th to 18th Century). The essay concludes that, across the study of the visual language put in the colonial polychromatic quero wooden cups (llimpisccaqueros), the actual investigators we can obtain indigenous narratives and opinions about colonial reality that, up to a point, are absent or minimized in the written records.